The Unconscious Self in Role Playing Video Game’s Avatar - Ardian Indro Yuwono; Gabriel Roosmargo Lono Lastoro Simatupang; Aprinus Salam (Jurnal Ilmu Komunikasi, 2018)
In the world of digital video games, human players are present through surrogates. Surrogates in the video game is a character which also called by the term avatar which is a self-representation of real players. The presence of avatars in role playing games are formed through a process of creation by the gamer. The production of avatars cannot be separated from the unconscious mind of the players, the unconscious desire, ego and ideology. This avatar creation process continues ongoing, following the progress of the video game story. The decision, the path, and the act that the player take in completing the story are gradually reshaping the avatar. In the end, the avatar eventually became a manifestation and reflection of the unconscious minds of the video game players. This research conducted using ethnography and Jacques Lacan psychoanalysis theory.